Regenerated positive electrode material and method for manufacturing same, method for using regenerated positive electrode material, regenerated
By preparing a regenerated positive electrode material containing specific metal elements and adopting a multi-step manufacturing method, the problems of large environmental burden and high cost in the reuse of lithium-ion secondary batteries are solved, and a high-performance regenerated lithium-ion secondary battery is realized.
Patent Information
- Application Number
- CN202380046413.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-17
- Filing Date
- 2023-05-29
- Publication Date
- 2025-02-07
AI Technical Summary
When reusing metal materials from lithium-ion secondary batteries that reach the end of product life, the prior art faces the problems of large environmental burden and high cost. At the same time, the performance of regenerated lithium-ion secondary batteries is difficult to achieve with the usual lithium-ion secondary batteries. Excellent level.
By preparing a recycled positive electrode material containing lithium, nickel, cobalt, manganese, aluminum, copper and iron, it is manufactured by heat treatment, crushing, physical screening, acid treatment, iron removal and alkali treatment, combined with a specific lithium source The addition and activation process improves the circulation characteristics of the battery.
Recycled positive electrode material manufactured with a small environmental burden and low reuse cost is achieved, with excellent performance compared to the usual lithium ion secondary battery positive electrode material, including the same specific capacity and better cycle characteristics.
Smart Images

Figure BDA0005182209950000201 
Figure BDA0005182209950000231 
Figure BDA0005182209950000232
Abstract
Description
Technical Field
[0001] The present invention relates to a regenerated positive electrode material and a method for producing the regenerated positive electrode material, a method for using the regenerated positive electrode material, a regenerated positive electrode and a lithium ion secondary battery. Background Art
[0002] The use of lithium-ion secondary batteries in the electronics field and the automotive field is rapidly expanding. In the automotive field, in particular, the demand for large batteries for hybrid vehicles and electric vehicles is expected to increase sharply due to the high capacity of batteries. As the demand for such lithium-ion secondary batteries increases, the number of lithium-ion secondary batteries that reach the end of their product life also increases.
[0003] On the other hand, lithium-ion secondary batteries use expensive metal materials as their positive electrode materials, and therefore, recycling the metal materials from lithium-ion secondary batteries that have reached the end of their product life is an important issue in terms of industry.
[0004] For example, a method for removing impurities from waste batteries, waste positive electrode materials, or mixtures thereof containing a metal group including at least two substances selected from Co, Ni, and Mn and impurities, and recovering the metal group in the form of a mixture of the metal salts has been proposed (for example, see Patent Document 1). In this proposal, the recovered mixture of metal salts is used to manufacture a positive electrode material.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 5847742 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] However, in order to reuse metal materials from lithium-ion secondary batteries that have reached the end of their product life, it is required that the environmental burden associated with the reuse is small and the reuse cost is low. In addition, when using nickel, cobalt, and manganese recovered from lithium-ion secondary batteries that have reached the end of their product life to manufacture positive electrode materials, it is required that the regenerated lithium-ion secondary batteries manufactured using the positive electrode materials have excellent performance that is no less than that of conventional lithium-ion secondary batteries (hereinafter, lithium-ion secondary batteries whose positive electrode materials do not use metal materials reused from lithium-ion secondary batteries are referred to as "conventional lithium-ion secondary batteries"). However, for example, the methods described in Patent Document 1 often use complex separation processes and high-cost extractants, and there are concerns that the environmental burden associated with the reuse is large and the cost is high.
[0010] The subject of the present invention is to solve various problems in the past and achieve the following purpose. That is, the purpose of the present invention is to provide a regenerated positive electrode material and a method for manufacturing the regenerated positive electrode material, which can be manufactured from a lithium ion secondary battery that has reached the end of its product life with a small environmental burden and a low recycling cost and has excellent performance comparable to that of a positive electrode material of a conventional lithium ion secondary battery, as well as a method for using the regenerated positive electrode material, a regenerated positive electrode and a lithium ion secondary battery.
[0011] Solutions for solving problems
[0012] The means for solving the above-mentioned problems are as follows.
[0013] <1> A regenerated positive electrode material, characterized in that it contains:
[0014] lithium, nickel, cobalt and manganese;
[0015] 0.3 mass % to 3 mass % aluminum; and
[0016] Less than 1 mass % of at least one of copper and iron.
[0017] <2> According to the aforementioned <1> The regenerated positive electrode material contains at least one of calcium and magnesium, and the content of at least one of the calcium and the magnesium is 0.02 mass % or more and 0.1 mass % or less.
[0018] <3> According to the aforementioned <1> or <2> The regenerated positive electrode material, wherein the content of the aluminum is greater than or equal to 0.5 mass % and less than or equal to 2.5 mass %.
[0019] <4> According to the aforementioned <1> or <2> The regenerated positive electrode material, wherein the content of the lithium is greater than 5 mass % and less than 9 mass %.
[0020] <5> According to the aforementioned <1> or <2> The regenerated positive electrode material, wherein
[0021] The copper content is 0.01 mass % or less.
[0022] The iron content is 0.6 mass % or less.
[0023] <6> According to the aforementioned <5> The regenerated positive electrode material, wherein
[0024] The copper content is 0.0005 mass % or more and 0.005 mass % or less,
[0025] The iron content is 0.002 mass % or more and 0.6 mass % or less.
[0026] <7> According to the aforementioned <1> or <2> The regenerated positive electrode material, wherein the content (mass %) of the aforementioned aluminum (Al), the content (mass %) of the aforementioned copper (Cu) and the content (mass %) of iron (Fe) satisfy the following formula: Al / (Al+Cu+Fe)≥0.4.
[0027] <8> According to the aforementioned <1> or <2> The regenerated positive electrode material contains the nickel, cobalt and manganese in an amount of 50% by mass or more in total.
[0028] <9> A method for manufacturing a regenerated positive electrode material, characterized in that it is to manufacture the aforementioned <1> or <2> The method for regenerating positive electrode material comprises the following steps:
[0029] A heat treatment step of heat-treating the lithium-ion secondary battery to obtain a heat-treated product;
[0030] A crushing step to obtain a crushed product by crushing the aforementioned heat-treated product;
[0031] A physical screening step, wherein the crushed material is physically screened to obtain a physically processed material;
[0032] an acid treatment step, adding an acid solution to the aforementioned physically treated product to obtain an acid treatment solution;
[0033] an iron removal step, wherein an oxidant is added to the acid treatment solution, an alkali solution is added, and the precipitation of iron hydroxide is filtered out; and
[0034] In the alkali treatment step, the filtrate after the iron removal step is mixed with an alkali solution.
[0035] <10> According to the aforementioned <9> The method for manufacturing the regenerated positive electrode material comprises: a lithium source adding step of adding a lithium source.
[0036] <11> A method for using a regenerated positive electrode material, characterized in that it comprises the following steps:
[0037] Assembling process, assembling the aforementioned <1> or <2> The lithium-ion secondary battery of the regenerated positive electrode material; and
[0038] In the activation step, the lithium ion secondary battery assembled in the above-mentioned assembly step is charged from a battery voltage of approximately 0V to 4.3V to 4.6V, and then charged and discharged within a battery voltage range of 0V to 3.5V to 4.3V to 4.6V.
[0039] <12> A regenerated positive electrode, characterized in that it comprises the aforementioned <1> or <2> The regenerated positive electrode material.
[0040] <13> A lithium ion secondary battery, characterized in that it has the above <12> The regenerated positive electrode.
[0041] Effects of the Invention
[0042] According to the present invention, various previous problems can be solved, and a regenerated positive electrode material and a method for manufacturing the regenerated positive electrode material can be provided, which can be manufactured from lithium-ion secondary batteries that have reached the end of their product life with a small environmental burden and low recycling cost and has excellent performance that is no less than that of the positive electrode materials of conventional lithium-ion secondary batteries, as well as a method for using the regenerated positive electrode material, a regenerated positive electrode and a lithium-ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a flow chart showing an example of the method for producing a regenerated positive electrode material of the present invention.
[0044] Figure 2 This is a schematic diagram showing an example of a button cell type lithium ion secondary battery used in Examples.
[0045] Figure 3 This is a graph showing the relationship between the number of cycles in the cycle test of the full battery of Example 1 and the specific capacity of the positive electrode material.
[0046] Figure 4 This is a graph showing the relationship between the number of cycles in the cycle test of the full battery of Comparative Example 1 and the specific capacity of the positive electrode material.
[0047] Figure 5 This is a graph showing the relationship between the number of cycles in the cycle test of the full battery of Comparative Example 2 and the specific capacity of the positive electrode material.
[0048] Figure 6 This is a graph showing the relationship between the specific capacity of the positive electrode material and the battery voltage in the cycle test of the full battery of Example 1.
[0049] Figure 7 This is a graph showing the relationship between the specific capacity of the positive electrode material and the battery voltage in the cycle test of the full battery of Comparative Example 1.
[0050] Figure 8 This is a graph showing the relationship between the specific capacity of the positive electrode material and the battery voltage in the cycle test of the full battery of Comparative Example 2. DETAILED DESCRIPTION
[0051] (Regenerated positive electrode material)
[0052] The regenerated positive electrode material of the present invention contains lithium, nickel, cobalt and manganese; 0.3 mass % to 3 mass % of aluminum; and less than 1 mass % of at least one of copper and iron, and further contains other components as needed.
[0053] The regenerated positive electrode material of the present invention and the lithium ion secondary battery obtained using the aforementioned regenerated positive electrode material are charged and discharged at an upper limit battery voltage that is 0.1V to 0.4V higher than the upper limit battery voltage of 4.2V in normal charge and discharge, so that Li is easily separated from the regenerated positive electrode, and the Li separated once can be repeatedly separated / embedded thereafter, and can show the same level of specific capacity as a lithium ion secondary battery obtained using a conventional positive electrode material (hereinafter, the positive electrode material that does not use a metal material recycled from a lithium ion secondary battery is referred to as a "conventional positive electrode material"), and can achieve better cycle characteristics than a lithium ion secondary battery obtained using a conventional positive electrode material.
[0054] In the present invention, the aforementioned lithium, the aforementioned nickel, the aforementioned cobalt, the aforementioned manganese, the aforementioned aluminum, the aforementioned copper and the aforementioned iron include the metal elements of lithium, nickel, cobalt, manganese, aluminum, copper and iron, and also include the metal elements contained in the oxides or hydroxides (i.e., compounds bonded with other elements) of the metal elements. In addition, "oxide" or "hydroxide" includes at least any one of the respective metal oxides or metal hydroxides, and the composite oxides containing the respective metal elements or the composite hydroxides containing the respective metal elements.
[0055] The aluminum content is 0.3% to 3% by mass, preferably 0.5% to 2.5% by mass, and more preferably 0.7% to 1.5% by mass. If the aluminum content is 0.3% to 3% by mass, the battery voltage is 0.1V to 0.4V higher than the upper limit battery voltage of 4.2V in normal charge and discharge, and the cycle characteristics of the lithium ion secondary battery obtained by using the usual positive electrode material are better than those of the usual positive electrode material of the lithium ion secondary battery.
[0056] The lithium content is preferably 4% by mass or more and 10% by mass or less, more preferably 5% by mass or more and 9% by mass or less, and even more preferably 7% by mass or more and 8.5% by mass or less.
[0057] The total content of nickel, cobalt and manganese is preferably 50% by mass or more, more preferably 55% by mass or more. The respective contents of nickel, cobalt and manganese can be adjusted according to the characteristics of the target battery. For example, if it is a positive electrode material for NCM811, nickel may be contained at 15% by mass or more and 52% by mass or less, cobalt may be contained at 6% by mass or more and 25% by mass or less, and manganese may be contained at 6% by mass or more and 25% by mass or less. In addition, if it is a positive electrode material for NCM111, nickel, cobalt and manganese may be contained at 10% by mass or more and 30% by mass or less, respectively.
[0058] The regenerated positive electrode material of the present invention contains less than 1% by mass of at least one of copper and iron.
[0059] The copper content is less than 1% by mass, preferably 0.01% by mass or less, and more preferably 0.0005% by mass or more and 0.005% by mass or less.
[0060] The iron content is less than 1 mass %, preferably 0.6 mass % or less, and more preferably 0.002 mass % or more and 0.6 mass % or less.
[0061] If it contains less than 1% by mass of at least one of copper and iron, it shows better cycle characteristics than a lithium ion secondary battery obtained using a conventional positive electrode material within the range of an upper limit battery voltage of 0.1V to 0.4V higher than the upper limit battery voltage of 4.2V in normal charge and discharge, and is significantly different from the positive electrode material of a conventional lithium ion secondary battery.
[0062] It is preferable to contain at least one of calcium and magnesium. The content of at least one of calcium and magnesium is preferably 0.02 mass % or more and 0.1 mass % or less, and more preferably 0.04 mass % or more and 0.09 mass % or less.
[0063] When metals recycled from lithium-ion secondary batteries are used, calcium and magnesium are often contained. However, it has been confirmed that such contents have no significant effect on the battery characteristics obtained by using recycled positive electrode materials.
[0064] The aluminum (Al) content (mass %), the copper (Cu) content (mass %) and the iron (Fe) content (mass %) preferably satisfy the following formula: Al / (Al+Cu+Fe)≥0.4, more preferably satisfy the following formula: Al / (Al+Cu+Fe)≥0.5, further preferably satisfy the following formula: Al / (Al+Cu+Fe)≥0.6, particularly preferably satisfy the following formula: Al / (Al+Cu+Fe)≥0.7, more particularly preferably satisfy the following formula: Al / (Al+Cu+Fe)≥0.8, and further particularly preferably satisfy the following formula: Al / (Al+Cu+Fe)≥0.9.
[0065] By satisfying the following formula: Al / (Al+Cu+Fe)≥0.4, the battery exhibits cycle characteristics superior to those of a normal lithium ion secondary battery within a range of an upper limit battery voltage of 0.1 to 0.4 V higher than the upper limit battery voltage of 4.2 V in normal charge and discharge.
[0066] The content of each metal element can be measured by, for example, ICP analysis or fluorescent X-ray analysis.
[0067] <Other ingredients>
[0068] There are no particular limitations on other components, and other components may be contained within a range in which the effects of the present invention are exhibited. Examples thereof include Na, O, and fluorine (F).
[0069] The regenerated positive electrode material of the present invention containing lithium, nickel, cobalt and manganese, and containing 0.3% by mass or more and 3% by mass or less of aluminum, and less than 1% by mass of at least one of copper and iron can be suitably produced by the method for producing the regenerated positive electrode material of the present invention described below.
[0070] (Method for producing recycled positive electrode material)
[0071] The method for manufacturing the regenerated positive electrode material of the present invention is a method for manufacturing the regenerated positive electrode material of the present invention, which includes a heat treatment step, a crushing step, a physical screening step, an acid treatment step, an iron removal step and an alkali treatment step, preferably including a lithium source addition step, and further including other steps as needed.
[0072] Here, Figure 1 1 is a flow chart showing an example of a method for producing a regenerated positive electrode material according to the present invention. Figure 1 , the method for producing the regenerated positive electrode material of the present invention is described.
[0073] <Lithium Ion Secondary Battery as Processing Object>
[0074] There is no particular limitation on the lithium-ion secondary batteries to be processed, and they can be appropriately selected according to the purpose. Examples include defective lithium-ion secondary batteries produced during the manufacturing process of lithium-ion secondary batteries; lithium-ion secondary batteries discarded due to poor use of the machine, the life of the machine, etc.; used lithium-ion secondary batteries discarded due to their lifespan, etc.
[0075] Lithium-ion secondary batteries are secondary batteries that are charged and discharged by the movement of lithium ions between a positive electrode and a negative electrode, and include, for example, a secondary battery comprising a positive electrode, a negative electrode, a separator, an electrolyte (an electrolyte solution containing an organic solvent or a solid electrolyte), and an outer container as a battery case.
[0076] The shape, structure, size, material, etc. of the lithium ion secondary battery of the processing object are not particularly limited and can be appropriately selected according to the purpose. As the shape of the lithium ion secondary battery, for example, laminated type, cylindrical type, button type, coin type, square type, flat type, etc. can be listed.
[0077] -positive electrode-
[0078] The positive electrode is not particularly limited as long as it has a positive electrode material on a positive electrode current collector, and can be appropriately selected according to the purpose. The shape of the positive electrode is not particularly limited, and can be appropriately selected according to the purpose, and examples thereof include a flat plate shape, a sheet shape, and the like.
[0079] As the positive electrode current collector, there is no particular limitation on its shape, structure, size, material, etc., and it can be appropriately selected according to the purpose. As the shape of the positive electrode current collector, for example, foil can be listed. As the material of the positive electrode current collector, for example, stainless steel, nickel, aluminum, copper, titanium, tantalum, etc. can be listed. Among these, aluminum is mostly used.
[0080] The constituent members of the positive electrode material can be appropriately selected according to the purpose, and examples thereof include positive electrode active materials containing at least rare valuable items, and positive electrode materials containing conductive agents and binding resins as required. Rare valuable items are not particularly limited and can be appropriately selected according to the purpose, and cobalt, nickel, and manganese are mostly used.
[0081] Examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), and lithium cobalt nickel oxide (LiCoO2). 1 / 2 Ni 1 / 2 O2), ternary materials ("NMC", namely LiNi x Co y Mn z O2, x+y+z=1, and x, y, z are respectively greater than 0 and less than 1), nickel-based materials ("NCA", i.e. LiNi x Co y Al z O2, x+y+z=1, and x, y, z are respectively greater than 0 and less than 1), or a complex of any combination thereof, x+y+z=1, and x, y, z are respectively greater than 0 and less than 1, etc.
[0082] The conductive agent is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include carbon black, graphite, carbon fibers, and metal carbides.
[0083] The binder resin is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include homopolymers or copolymers of vinylidene fluoride, tetrafluoroethylene, acrylonitrile, ethylene oxide, and the like, and styrene-butadiene rubber.
[0084] -negative electrode-
[0085] The negative electrode is not particularly limited as long as it has a negative electrode material on a negative electrode current collector, and can be appropriately selected according to the purpose. The shape of the negative electrode is not particularly limited, and can be appropriately selected according to the purpose, and examples thereof include a flat plate shape, a sheet shape, and the like.
[0086] As the negative electrode current collector, there is no particular limitation on its shape, structure, size, material, etc., and it can be appropriately selected according to the purpose. As the shape of the negative electrode current collector, for example, foil can be listed. As the material of the negative electrode current collector, for example, stainless steel, nickel, aluminum, copper, titanium, tantalum, etc. can be listed. Among these, copper is preferred.
[0087] The negative electrode material is not particularly limited and can be appropriately selected depending on the intended purpose. Examples thereof include carbon materials such as graphite and hard carbon, titanate, silicon, and composites thereof.
[0088] The positive electrode current collector and the negative electrode current collector have a laminate structure, and the laminate is not particularly limited and can be appropriately selected depending on the intended purpose.
[0089] <Heat treatment process>
[0090] The heat treatment step is a step of obtaining a heat-treated product by heat-treating the lithium-ion secondary battery.
[0091] like Figure 1 As shown, first, the lithium ion secondary battery as the treatment object is subjected to a heat treatment process. The heat treatment temperature is not particularly limited as long as it is a temperature above the melting point of the collector with a low melting point among the positive electrode collector and the negative electrode collector and below the melting point of the collector with a high melting point. It can be appropriately selected according to the purpose, preferably above 670°C, more preferably above 670°C and below 1100°C, further preferably above 700°C and below 1000°C, and particularly preferably above 700°C and below 900°C. If the heat treatment temperature is above 670°C, the embrittlement of the collector with a low melting point occurs fully. If it is below 1100°C, the collector with a low melting point, the collector with a high melting point and the outer packaging container can all suppress embrittlement, and the separation efficiency of the collector and the outer packaging container by crushing and grading can be maintained. Furthermore, when the outer container of the lithium ion secondary battery melts during the heat treatment, a receiving dish for recovering the molten metal is disposed below the lithium ion secondary battery, thereby making it easy to separate the metal derived from the outer container and the electrode portion.
[0092] By performing heat treatment at a predetermined heat treatment temperature, in a laminate in which, for example, the positive electrode collector is aluminum foil and the negative electrode collector is copper, the positive electrode collector formed by the aluminum foil becomes brittle and is easily granulated in the crushing process described later. The embrittlement of the positive electrode collector occurs due to melting or oxidation reaction. In addition, the aluminum that melts and flows down is recovered in the receiving dish. On the other hand, the negative electrode collector formed by copper is heat treated at a temperature lower than the melting point of copper, so it can be highly screened in the magnetic screening process described later without melting. In addition, when either the laminate or the lithium ion secondary battery is placed in an oxygen isolation container and heat treated, the positive electrode collector formed by the aluminum foil melts and becomes brittle, and is easily granulated in the crushing process described later. On the other hand, the negative electrode collector formed by copper is heat treated under a low oxygen partial pressure by virtue of the oxygen isolation effect of the aforementioned oxygen isolation container and the reduction effect achieved by the negative electrode active materials such as carbon contained in the laminate and the lithium ion secondary battery, so it will not become brittle due to oxidation. Therefore, the positive electrode current collector is crushed into fine particles by the crushing in the crushing step, and the negative electrode current collector is also present as coarse particles after crushing, and can be more efficiently and highly screened in the classification and screening step described later.
[0093] As heat treatment time, it is not particularly limited, and can be appropriately selected according to the purpose, preferably more than 1 minute and less than 5 hours, more preferably more than 1 minute and less than 2 hours, and particularly preferably more than 1 minute and less than 1 hour. The heat treatment time is the heat treatment time until the aforementioned collector with a low melting point reaches the desired temperature, and the holding time can also be shorter. If the heat treatment time is within a particularly preferred range, it is advantageous in terms of the cost of heat treatment.
[0094] The heat treatment method is not particularly limited and can be appropriately selected according to the purpose, and for example, a heat treatment furnace can be used. Examples of the heat treatment furnace include intermittent furnaces such as rotary kilns, fluidized bed furnaces, tunnel furnaces, and muffle furnaces; cupola furnaces, stoker furnaces, and the like.
[0095] The atmosphere used in the heat treatment is not particularly limited and can be appropriately selected according to the purpose, and can be carried out in air. If it is set to an atmosphere with a low oxygen concentration, it is preferred from the viewpoint of being able to recover the metal from the positive electrode collector and the metal from the negative electrode collector with high quality and high recovery rate.
[0096] As a method for achieving the above-mentioned low oxygen atmosphere, a lithium ion secondary battery or a stack can be placed in an oxygen-insulated container and heat-treated. As the material of the oxygen-insulated container, there is no particular limitation as long as it is a material that does not melt at the above-mentioned heat treatment temperature, and it can be appropriately selected according to the purpose, and examples thereof include iron, stainless steel, etc. In order to release the gas pressure caused by the combustion of the electrolyte in the lithium ion secondary battery or the stack, an opening is preferably provided in the oxygen-insulated container. It is preferably provided in a manner that the opening area of the opening is less than 12.5% relative to the surface area of the outer packaging container provided with the opening. The opening area of the opening is more preferably less than 6.3% relative to the surface area of the outer packaging container provided with the opening. If the opening area of the opening exceeds 12.5% relative to the surface area of the outer packaging container, most of the collector is easily oxidized due to the heat treatment. There are no particular limitations on the shape, size, formation location, etc. of the opening, and it can be appropriately selected according to the purpose.
[0097] Here, it is also preferred to perform qualitative and quantitative analysis of the metal elements contained in the heat-treated product obtained by the heat treatment process using fluorescent X-ray analysis, etc. This is because the metal components contained in the heat-treated product may differ depending on the lithium-ion secondary battery to be treated.
[0098] From the viewpoint of stabilizing the composition of the metal component of the regenerated positive electrode material, a preferred configuration is to group the heat-treated products having the same metal component composition based on the qualitative and quantitative analysis results, and to transport the heat-treated products divided into groups to the crushing step described later.
[0099] <Crushing process>
[0100] The crushing step is a step of crushing the heat-treated product to obtain a crushed product.
[0101] As a method of crushing by impact, for example, there can be listed: a method of throwing a rotating striking plate to hit the impact plate to apply an impact; a method of hitting the heat-treated object with a rotating beater, which can be performed using, for example, a hammer crusher, a chain crusher, etc. In addition, there can be listed a method of hitting the heat-treated object with balls or rods made of ceramics, iron, etc., which can be performed using a ball mill, a rod mill, etc. In addition, it can be performed by crushing using a double-shaft crusher with a short blade width and blade length that is crushed based on compression.
[0102] By using impact to obtain the crushed product, the crushing of the active material and the low-melting point current collector is promoted, while the high-melting point current collector whose shape has not changed significantly exists in the form of foil, etc. Therefore, in the crushing process, the high-melting point current collector is only cut, and the high-melting point current collector is not easy to be finely granulated compared with the low-melting point current collector. Therefore, in the classification and screening process described later, the crushed product in a state that the low-melting point current collector and the high-melting point current collector can be effectively separated can be obtained.
[0103] As the crushing time, there is no particular limitation, and it can be appropriately selected according to the purpose. The processing time per 1kg lithium ion secondary battery is preferably more than 1 second and less than 30 minutes, more preferably more than 2 seconds and less than 10 minutes, and particularly preferably more than 3 seconds and less than 5 minutes. If the crushing time is less than 1 second, it is sometimes not crushed, and if it exceeds 30 minutes, it is sometimes excessively crushed. In addition, it is preferred that the maximum particle size of the crushed object is set to less than 10mm.
[0104] <Physical Screening Process>
[0105] The physical screening step is a step of physically screening the crushed product to obtain a physically treated product.
[0106] -Grading and screening process-
[0107] As a physical screening process, a classification screening process can be performed to classify the crushed product obtained by the crushing process into a coarse particle product and a fine particle product. There is no particular limitation on the classification method, and it can be appropriately selected according to the purpose. For example, a vibrating screen, a multi-stage vibrating screen, a cyclone separator, a standard screen of JIS Z8801, a wet vibrating table, a pneumatic table, etc. can be used.
[0108] As the classification point used in the classification and screening process, there is no particular limitation, and it can be appropriately selected according to the purpose, preferably 0.45 mm or more, more preferably 0.6 mm or more and 2.4 mm or less. If the classification point exceeds 2.4 mm, the metals from the outer packaging container and the higher melting point mixed into the fine-grained product will increase, and the separation results from the cobalt and nickel from the active material will decrease. On the other hand, if the classification point is less than 0.45 mm, the metals from the collector with a low melting point and the active material mixed into the coarse-grained product will increase, and the quality of the metals from the collector with a high melting point in the coarse-grained product will decrease, and the recovery rate of cobalt and nickel from the active material in the fine-grained product will be less than 60%. In addition, when using a sieve as a classification method, by placing a pulverizing promoter, such as a stainless steel ball or an alumina ball on the sieve and sieving, the small crushed objects attached to the large crushed objects are separated from the large crushed objects, thereby, it is possible to more effectively separate into large crushed objects and small crushed objects. The quality of the recovered metal can thus be further improved. It should be noted that the crushing step and the classification and screening step may also be performed simultaneously. For example, the crushing step may be performed while the heat-treated product obtained in the heat treatment step is crushed and the crushed product is classified into a coarse-grained product and a fine-grained product (crushing / classification).
[0109] Through the above classification, the metals derived from the outer packaging container and the collector with a high melting point can be recovered as coarse-grained products, and the concentrates of cobalt, nickel, and lithium derived from the active material can be recovered as fine-grained products (black powder (black mass)). It should be noted that the fine-grained products can be classified again. By utilizing this re-classification to remove fine particles such as 150 μm or less from the fine-grained products, the amount of negative electrode active material contained in the non-magnetic adsorbent of wet magnetic screening (hereinafter sometimes magnetic screening is referred to as "magnetic separation") can be reduced.
[0110] -Magnetic separation process-
[0111] As a physical screening step, the crushed product obtained in the crushing step or the coarse particle product obtained in the classification screening step can be subjected to a dry magnetic separation step to recover iron as a magnetically attracted product and recover metals such as copper derived from the negative electrode current collector as a non-magnetically attracted product.
[0112] As the physical screening step, it is more preferable to perform a wet magnetic separation step (wet magnetic separation) on the crushed product obtained in the crushing step or the fine particle product (black powder) obtained in the classification screening step, and recover the cobalt and nickel concentrate in the form of magnetically attracted products.
[0113] When the fine-particle product obtained by the grading and screening process is subjected to magnetic separation, in the case of dry magnetic separation, the particles aggregate due to the attached moisture between the particles, and the metal particles derived from the negative electrode collector and more than 10% by mass of the negative electrode active material particles contained in the fine-particle product cannot be fully separated from the cobalt and nickel particles. In the present invention, in the wet magnetic separation process, the substance derived from the negative electrode active material and the metal derived from the negative electrode collector are separated into a non-magnetic adsorbent slurry, and the cobalt and nickel are recovered into the magnetic adsorbent to obtain a physically treated product. It should be noted that manganese is not strongly magnetic at room temperature, but when it forms a composite oxide with cobalt and nickel in a lithium-ion secondary battery, it is attached during the magnetic separation of cobalt and nickel. Therefore, a large amount of manganese is also recovered in the magnetic separation. The magnetic force during magnetic separation is preferably 1,500G to 8,000G.
[0114] On the other hand, lithium is dissolved in the liquid during the slurrying of the raw materials and the wet magnetic separation, and is separated into the non-magnetic slurry. By performing solid-liquid separation on the non-magnetic slurry, the metal and negative electrode active material derived from the negative electrode collector can be separated into the residue. In addition, carbon dioxide is blown into the liquid separated by solid-liquid separation, precipitated in the form of lithium carbonate, and lithium is recovered. It should be noted that before blowing the aforementioned carbon dioxide, a pre-treatment process such as a liquid concentration process may be performed for the purpose of removing impurities and increasing the lithium concentration. For example, fluorine and the like are recovered in the residual liquid. Therefore, the quality of fluorine in the physical treatment product can be less than 1%. Leaching treatment is required to recover lithium and separate fluorine from cobalt and nickel, but in the present invention, in the wet magnetic separation process, water leaching of lithium and leaching removal of fluorine and separation of cobalt and nickel in the metal derived from the negative electrode collector can be performed simultaneously, and from this point of view, the number of processes can be reduced.
[0115] <Acid treatment process>
[0116] The acid treatment step is a step of adding an acid solution to the physically treated product to obtain an acid treatment solution.
[0117] This is a process of adding an acid such as HCl, HNO3, or H2SO4 to the physical treatment product to dissolve the metal element in the acidic solution.
[0118] For example, the physically treated material after adding the acid is heated at 20°C to 180°C for 0.1 to 3 hours, and the metal elements in the physically treated material are thermally decomposed and dissolved in the acidic solution. After the thermal decomposition is completed, the acidic solution is naturally cooled, the acidic solution is filtered to remove the insoluble residue in the acidic solution, and the filtrate is recovered. It should be noted that, as an acid, in addition to being used alone, it can also be a composition in which, for example, HCl is added to the physically treated material and heated, and then HNO3 is added and heated.
[0119] As the filtering method, various methods such as membrane filter, filter paper, etc. can be used. In addition, cross-flow filtration is also preferably used.
[0120] <Iron Removal Process>
[0121] The iron removal step is a step of adding an oxidizing agent to the acid treatment solution, adding an alkaline solution, and filtering out the precipitate of iron hydroxide.
[0122] An oxidant (hydrogen peroxide) is added to the acid treatment solution after the acid treatment step to adjust the redox potential to the positive side of 500 mVEh / V. Thereafter, an alkaline solution is added to the acid treatment solution having the redox potential adjusted to adjust the pH to 3 to 5.5 to generate a precipitation of iron hydroxide. The filtrate and the iron hydroxide precipitate are filtered.
[0123] As the filtering method, various methods such as membrane filter, filter paper, etc. can be used. In addition, cross-flow filtration is also preferably used.
[0124] <Alkali treatment step>
[0125] The alkali treatment step is a step of mixing the filtrate after the above-mentioned iron removal step with an alkali solution.
[0126] This is a step of mixing the filtrate after the iron removal step with an alkaline solution to adjust the pH to 9 to 14, and causing the metal elements in the filtrate to form hydroxide precipitation.
[0127] For example, a 0.5 mol / L to 10 mol / L NaOH aqueous solution is added to the recovered filtrate as an alkali solution to adjust the pH of the filtrate to 9 to 14 to generate a hydroxide precipitate. After the addition of the alkali is completed, the filtrate is filtered to recover the hydroxide precipitate.
[0128] As the filtering method, various methods such as membrane filter, filter paper, etc. can be used. In addition, cross-flow filtration is also preferably used.
[0129] A process for washing the recovered hydroxide precipitate to obtain a regenerated positive electrode material precursor. For example, the recovered hydroxide precipitate is heated to 20°C to 200°C for 0.1 hour to 48 hours, and subjected to strong heat drying to obtain a dried product. The dried product is crushed to obtain a crushed product. An equal amount to 10 times the amount (by weight) of water is added to the crushed product to obtain a slurry. The obtained slurry is filtered to recover the hydroxide precipitate.
[0130] As the filtering method, various methods such as membrane filter, filter paper, etc. can be used. In addition, cross-flow filtration is also preferably used.
[0131] The recovered hydroxide precipitate is heated at 20° C. to 200° C. for 0.1 to 48 hours and dried to obtain a regenerated positive electrode material precursor.
[0132] The obtained regenerated positive electrode material precursor is a solid (solid). In the subsequent process, the regenerated positive electrode material precursor can be processed in the form of a solid or slurried. Even in the case of slurry, the regenerated positive electrode material precursor contained in the slurry is a solid.
[0133] It should be noted that the salt remaining in the hydroxide precipitate can be removed by adding a lithium source to the regenerated positive electrode material precursor in the subsequent stage and then washing it.
[0134] <Lithium source adding process>
[0135] The lithium source adding step is a step of adding a regenerated positive electrode material precursor and a predetermined amount of a lithium source.
[0136] Examples of the lithium source include lithium carbonate, lithium hydroxide, lithium nitrate, and lithium chloride.
[0137] The amount of the lithium source added is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.8 equivalents or more and 2.0 equivalents or less relative to the total amount of hydroxides of metal elements functioning as a positive electrode material contained in the regenerated positive electrode material precursor.
[0138] <Pulverizing and mixing process>
[0139] The pulverizing and mixing step is a step of pulverizing the mixture to which a predetermined amount of lithium source is added.
[0140] The mixture to which a predetermined amount of lithium source is added is pulverized to obtain a pulverized mixture. The pulverization can be performed using, for example, a disk mill, a stirring mill, a bead mill, a vibration mill, a ball mill, a planetary ball mill, an attritor, or the like.
[0141] <Calcination process>
[0142] The obtained pulverized mixture is calcined in an alumina crucible under an atmospheric atmosphere at 600°C for 1 hour and then at 900°C for 4 hours to obtain a calcined product. The holding temperature of the calcination is preferably 650°C to 900°C. The holding time of the calcination is preferably 0.1 hour to 20 hours, more preferably 0.5 hour to 8 hours. In the regenerated positive electrode material after calcining the regenerated positive electrode material precursor, iron, copper and aluminum are oxidized. Specifically, iron, copper and aluminum, which are mostly hydroxides in the regenerated positive electrode material precursor, form oxides.
[0143] <Crushing process>
[0144] The obtained calcined product is pulverized using a disk mill or the like to obtain the regenerated positive electrode material of the present invention.
[0145] It should be noted that, as described above, the pulverized product after calcination may be subjected to a washing process. In this case, the calcination step may be performed again after the washing process to obtain a regenerated positive electrode material.
[0146] The obtained regenerated positive electrode material of the present invention contains: lithium, nickel, cobalt and manganese; 0.3% by mass or more and 3.0% by mass or less of aluminum; and less than 1% by mass of at least one of copper and iron, which can exhibit the same level of specific capacity as a lithium ion secondary battery obtained using a conventional positive electrode material, and can achieve better cycle characteristics than a lithium ion secondary battery obtained using a conventional positive electrode material.
[0147] In the method for producing a regenerated positive electrode material of the present invention, the regenerated positive electrode material of the present invention can be used as a raw material.
[0148] When the composition of the metal element that functions as the target positive electrode material in the regenerated positive electrode material is different from the composition of the metal element of the obtained regenerated positive electrode material of the present invention, the composition of the metal element of the regenerated positive electrode material can be adjusted. That is, the regenerated positive electrode material of the present invention can be used as a raw material to manufacture the regenerated positive electrode material.
[0149] As a method for adjusting the composition of the aforementioned metal elements, for example, a method of appropriately mixing physical treatment products having different compositions of metal elements, a method of adding insufficient metal elements, etc. The specific amount of addition can be determined based on the qualitative and quantitative analysis results of the metal elements contained in the physical treatment product based on ICP analysis or fluorescent X-ray analysis.
[0150] (Method of using recycled positive electrode material)
[0151] The method for using the regenerated positive electrode material of the present invention comprises:
[0152] An assembling step of assembling a lithium-ion secondary battery having the regenerated positive electrode material of the present invention; and
[0153] The activation step charges the lithium ion secondary battery assembled in the above-mentioned assembly step from a battery voltage of approximately 0 V to 4.3 V to 4.6 V, and then performs charge and discharge in a battery voltage range of 0 V to 3.5 V to 4.3 V to 4.6 V, and further includes other steps as necessary.
[0154] As the activation step, it is preferred to charge and discharge at an upper limit battery voltage that is 0.1V to 0.4V higher than the upper limit battery voltage of 4.2V in normal charge and discharge, and more preferably 0.2V to 0.3V higher. Specifically, the charge and discharge cycle in the range of 0V to 3.5V to 4.3V to 4.6V with a higher upper limit battery voltage than the normal battery voltage range of 2.5V to 4.2V can be performed 1 to 5 times (preferably 3 times). From the viewpoint of the charge and discharge cycle time, the lower limit battery voltage is more preferably 1.5V to 3.5V, and more preferably 2.0V to 3.0V.
[0155] According to the method for using the regenerated positive electrode material of the present invention, by performing the activation step, it is possible to achieve cycle characteristics superior to those of a common positive electrode material for a lithium ion secondary battery.
[0156] (Regeneration positive electrode)
[0157] The regenerated positive electrode of the present invention contains the regenerated positive electrode material of the present invention, and further contains other components as necessary.
[0158] The regenerated positive electrode material of the present invention is contained as a positive electrode active material, and a conductive agent, a binder resin, etc. are contained as other components.
[0159] The regenerated positive electrode of the present invention has better cycle characteristics than the positive electrode materials of ordinary lithium ion secondary batteries by performing multiple charge and discharge cycles within the upper limit battery voltage range of 0.1V to 0.4V higher than the upper limit battery voltage of 4.2V in ordinary charge and discharge.
[0160] (Lithium-ion secondary battery)
[0161] The lithium ion secondary battery of the present invention is a lithium ion secondary battery comprising a positive electrode, a negative electrode, and a separator, and the positive electrode comprises the regenerated positive electrode material of the present invention.
[0162] The lithium ion secondary battery of the present invention can be manufactured by using the regenerated positive electrode material of the present invention and by a known lithium ion secondary battery method.
[0163] The lithium ion secondary battery of the present invention having the regenerated positive electrode material of the present invention has better cycle characteristics than lithium ion secondary batteries obtained using conventional positive electrode materials within the upper limit battery voltage range of 0V to 4.6V, which is 0.1V to 0.4V higher than the upper limit battery voltage of 4.2V during normal charge and discharge.
[0164] In addition, the lithium ion secondary battery of the present invention having the regenerated positive electrode material of the present invention expands the battery voltage range from 0V to 3.5V to 4.3V to 4.6V compared to the normal battery voltage range of 2.5V to 4.2V, so that Li is easily released from the regenerated positive electrode, and the Li released once can be repeatedly released / embedded thereafter, and can exhibit the same level of specific capacity as a lithium ion secondary battery obtained using a normal positive electrode material, and can achieve better cycle characteristics than a lithium ion secondary battery obtained using a normal positive electrode material.
[0165] Example
[0166] Hereinafter, examples of the present invention will be described, but the present invention is not limited to these examples at all.
[0167] (Comparative Example 1)
[0168] <Manufacturing of Recycled Positive Electrode Material>
[0169] -Heat treatment process-
[0170] A battery pack of lithium ion secondary batteries (about 75 kg) was heat treated at 800° C. (heating for 1 hour and then maintaining for 2 hours) using a batch combustion furnace of ECO-SYSTEM Akita Co., Ltd. as a heat treatment apparatus to obtain a heat-treated product.
[0171] - Crushing process -
[0172] Next, a hammer crusher (Makino-type pendulum crusher HC-20-3.7, manufactured by Makino Sangyo Co., Ltd.) was used as a crushing device. Under the conditions of 50 Hz (the circumferential speed of the hammer was 38 m / sec) and the wire mesh at the outlet was a grate-type opening of 30 mm × 200 mm, the heat-treated product (heat-treated lithium-ion secondary battery) obtained by the above-mentioned heat treatment step was crushed to obtain a crushed lithium-ion secondary battery.
[0173] -Grading process-
[0174] Next, the crushed product of the lithium ion secondary battery was sieved using a sieve with a mesh size of 1.2 mm (diameter 200 mm, manufactured by TOKYO SCREEN CO., LTD.), and was screened into an oversize product (coarse particle product) and an undersize product (medium particle product), and the crushed product was obtained in the form of an undersize product (medium particle product).
[0175] -Magnetic screening process-
[0176] The crushed product was subjected to wet magnetic separation using a drum-type magnetic separator under the conditions of magnetic force: 1500 G, drum rotation speed: 45 rpm, solid-liquid ratio: 10%, and slurry supply speed: 100 mL / min, and the physically treated product was recovered.
[0177] -Acid treatment process-
[0178] Put 5 g of the obtained physical treatment product into a 500 mL conical flask, add 100 mL of hydrochloric acid (12N), and use a hot plate at 70°C to 100°C to heat and decompose for 1 hour. At the end of the reaction, add 100 mL of ion exchange water, and then add 100 mL of HNO3 (14N) to make an acidic solution. And, use a hot plate at 160°C to heat and decompose for 1 hour until the reaction is completed. After the acidic solution is naturally cooled, use No. 5C filter paper to remove the insoluble residue in the acidic solution and recover the filtrate.
[0179] -Alkali treatment process-
[0180] Add an aqueous NaOH solution with a concentration of about 7.5% by mass to the recovered filtrate, adjust the pH to 12, and precipitate the hydroxide. And, use No.5C filter paper to recover the hydroxide. The recovered hydroxide is dried in a thermostatic bath at 105°C, crushed in a mortar, and put into a sufficient amount of ion exchange water, and washed to remove water-soluble salts. Use No.5C filter paper to recover the washed hydroxide, dry it in a thermostatic bath at 105°C, and obtain a regenerated positive electrode material precursor.
[0181] -Lithium source adding process-
[0182] The obtained regenerated positive electrode material precursor is added with lithium carbonate equivalent to 1.0 equivalent of the total amount of the hydroxides of cobalt, nickel and manganese contained, and the mixture is pulverized and mixed using a disc mill to obtain a pulverized mixture. The pulverized mixture is put into an alumina crucible and calcined under an atmospheric atmosphere at 600° C. for 1 hour and then at 800° C. for 4 hours to obtain a calcined product.
[0183] The calcined product was pulverized using a disk mill to obtain a regenerated positive electrode material of Comparative Example 1.
[0184] (Example 1)
[0185] Instead of the acid treatment step in Comparative Example 1, the following acid treatment step is performed, and the following iron removal step is performed between the aforementioned acid treatment step and the aforementioned alkali treatment step. To the obtained regenerated positive electrode material precursor is added lithium carbonate in an amount equivalent to 1.25 equivalents relative to the total amount of cobalt, nickel, and manganese hydroxides contained. Except for this, the same operations as in Comparative Example 1 are performed to obtain the regenerated positive electrode material of Example 1.
[0186] -Acid treatment process-
[0187] 30 g of the obtained physical treatment product was put into a 1000 mL upright beaker, and 1000 mL of sulfuric acid (20% by mass) was added to prepare an acidic solution. Then, the solution was heated and decomposed for 4 hours using a hot plate at 150° C. After the acidic solution was naturally cooled, the insoluble residue in the acidic solution was removed using No. 5C filter paper, and the filtrate was recovered.
[0188] -Iron Removal Process-
[0189] An oxidant (hydrogen peroxide) is added to the acid treatment solution after the acid treatment step to adjust the redox potential to 650 mV (Ag / AgCl). Thereafter, an alkaline solution is added to the acid treatment solution having the redox potential adjusted to adjust the pH to 4.7 to generate a precipitation of iron hydroxide. The filtrate and the iron hydroxide precipitate are filtered.
[0190] (Comparative Example 2)
[0191] A commercially available cobalt-nickel-manganese positive electrode material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, PLB-H1, Gelon LIBGroup Ltd.).
[0192] Next, each of the obtained regenerated positive electrode materials was subjected to acid decomposition using a mixed acid of HCl and HNO3, and then analyzed using ICP-AES (SPECTRO GREEN, manufactured by Hitachi High-Tech Science Corporation). The results are shown in Tables 1 and 2. It should be noted that the content of each element in Tables 1 and 2 is in mass %.
[0193] [Table 1]
[0194] Mn Co Ni Li Cu Fe Al Na Example 1 24.69 15.06 1880 824 0.00050 0.00327 1.06 .05122 Comparative Example 1 17.30 16.12 20.40 7.33 2.18 1.24 1.71 .03837 Comparative Example 2 1857 19.87 20.17 7.19 0 0.00088 0 .00729
[0195] [Table 2]
[0196]
[0197] <Battery Manufacturing>
[0198] (1) Manufacturing of positive electrode
[0199] As active materials, the regenerated positive electrode materials described in Example 1 and Comparative Examples 1 to 2 were prepared, as a conductive aid, acetylene black (DENKA BLACK, manufactured by DENKA Corporation) was prepared, as a binder, polyvinylidene fluoride (KF polymer F#9130, manufactured by KUREHA Corporation) was prepared, and as a solvent, N-methylpyrrolidone was prepared.
[0200] Furthermore, the regenerated positive electrode material: acetylene black: polyvinylidene fluoride = 80:10:10 (mass %) were mixed to prepare a mixture. N-methylpyrrolidone was added to the mixture to obtain a slurry. The amount of N-methylpyrrolidone added to the mixture was set to the mixture: N-methylpyrrolidone = 1:1.25 in terms of mass ratio.
[0201] The obtained slurry was stirred for 10 minutes with a stirrer, and then applied with a Baker-type applicator to prepare a coating, which was dried in a dryer at 100° C. The dried coating was then pressed at 4 tons and punched into a 15 mm diameter to prepare a positive electrode.
[0202] (2) Manufacturing of negative electrode
[0203] As an active material, graphite (CGB-10, manufactured by Nippon Graphite Industries, Co., Ltd.) was prepared, as a conductive additive, acetylene black (DENKA BLACK, manufactured by DENKA Corporation) was prepared, as a binder, carboxymethyl cellulose (CELLOGEN 7A, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) and styrene-butadiene rubber (TRD2001, manufactured by JSR Corporation) were prepared, and as a solvent, pure water was prepared.
[0204] Then, the mixture was prepared by mixing graphite: acetylene black: carboxymethyl cellulose: styrene-butadiene rubber in a ratio of 90:5:2.5:2.5 (mass %). Distilled water was added to the mixture to obtain a slurry. The amount of distilled water added to the mixture was set to the mixture: distilled water = 1:1.6 in terms of mass ratio.
[0205] The obtained slurry was stirred, applied, dried, pressed, and punched out in the same manner as in the production of the positive electrode to produce a negative electrode.
[0206] (3) Assembly of lithium-ion secondary batteries
[0207] In a glove box filled with pure argon gas, use a CR2032 button battery such as Figure 2As shown, the positive electrode collector 1, the positive electrode 2, the separator 3, the gasket 4, the negative electrode 5, the separator 6, the washer 7 and the negative electrode collector 8 are stacked in this order to assemble the full battery described in Example 1 and Comparative Examples 1 and 2. In the full battery, graphite is used as the active material, and the assumed specific capacity of graphite is set to 340 mAh / g.
[0208] It should be noted that the separator used was porous polypropylene (#2500, manufactured by Celgard LLC) with a diameter of φ19 mm, and LiPF6 with a concentration of 1 mol / L was used as the solute in the electrolyte, and ethylene carbonate + diethyl carbonate (volume ratio of 1:1) was used as the solvent.
[0209] In the case of a full battery, the assumed specific capacity of the normal positive electrode material and the recycled positive electrode material varies within the range of 100 mAh / g to 150 mAh / g depending on the battery voltage range during charge and discharge, but the ratio of the negative electrode capacity to the positive electrode capacity (NP ratio) is set to 1.2. The assumed specific capacity of the positive electrode material used in the full battery is clearly stated each time.
[0210] 3. Battery charge and discharge test
[0211] For the full batteries described in Example 1 and Comparative Examples 1 to 2, a charge and discharge test based on a cycle test was performed as follows to measure the charge and discharge specific capacity and coulomb efficiency (charge and discharge efficiency, hereinafter referred to as efficiency) of the regenerated positive electrode materials described in Example 1 and Comparative Examples 1 to 2. In the case of a full battery, the performance of the battery is evaluated by dividing the capacity measured during charging and discharging of the battery by the mass of the regenerated positive electrode material in the battery by the positive electrode reference specific capacity.
[0212] (1) Full battery charge and discharge test
[0213] (I) (Cycle test of full battery)
[0214] Charging and discharging were performed at a constant current density under the following conditions.
[0215] Test temperature: 25℃
[0216] Battery voltage range: 2.5V~4.2V (initial charge: 0V~4.2V)
[0217] Current density: 2C
[0218] Number of cycles: 500 cycles
[0219] The assumed specific capacity of common positive electrode materials: 140 mAh / g
[0220] Among them, 1C = 140mA / g-usual positive electrode material
[0221] Assumed specific capacity of recycled positive electrode material: 100mAh / g
[0222] Among them, 1C = 100mA / g-regenerated positive electrode material
[0223] The results of the relationship between the number of cycles and the specific capacity characteristics in the cycle test are shown in Figure 3 to Figure 5 and Table 3. In addition, the results of the relationship between the specific capacity and the battery voltage in the cycle test are shown in Figure 6 to Figure 8 Among them, Figure 3 to Figure 5 In the graph, the horizontal axis is the number of cycles, the left vertical axis is the specific capacity, and the right vertical axis is the efficiency. In addition, when the charge specific capacity is marked as □, the discharge specific capacity is marked as ◇, and the efficiency is marked as 0, the charge specific capacity: □ and the discharge specific capacity: ◇ are plotted overlappingly.
[0224] [Table 3]
[0225]
[0226] (II) (Cycle test of full battery, 2.5V to 4.4V (initial charge: 0V to 4.4V))
[0227] The battery voltage range was increased to 2.5 V to 4.4 V, and the cycle test was performed in the same manner as above. The assumed specific capacity of the positive electrode material was set to 150 mAh / g. Here, 1C = 150 mA / g. The results are shown in Table 4.
[0228] [Table 4]
[0229]
[0230] It is found that the effect of improving the cycle characteristics is greater than that of Comparative Examples 1 and 2 when charging and discharging is performed in advance within the range of the upper limit battery voltage which is 0.2 V higher than the upper limit battery voltage of 4.2 V in normal charging and discharging.
[0231] It can be seen that if the upper limit battery voltage is increased, that is, the potential of the positive electrode is further increased, Li is easily separated from the regenerated positive electrode of Example 1, and the Li separated once can be repeatedly separated / embedded thereafter. It can be seen that Example 1 can show a better specific capacity than Comparative Examples 1 and 2 when used in the normal battery voltage range of 2.5V to 4.2V, but when the upper limit battery voltage is set to a range of 2.5V to 4.4V, the effect of improving battery characteristics is more significant than that of Comparative Examples 1 and 2.
[0232] (III) (Full battery 2.5V to 4.4V, 0.1C, 3 cycles, cycle test 2.5V to 4.2V)
[0233] For the full battery of Example 1, after 3 cycles of charge and discharge at 2.5V to 4.4V (initial charge: 0V to 4.4V) and 0.1C, the cycle test was performed in the same manner as above within the battery voltage range of 2.5V to 4.2V. The assumed specific capacity of the positive electrode material was set to 140mAh / g. Among them, 1C = 140mA / g. The results are shown in Table 5.
[0234] (Example 2)
[0235] (IV) (Full battery 2.5V to 4.3V, 0.1C, 3 cycles, cycle test 2.5V to 4.2V)
[0236] For the full battery assembled in the same manner as in Example 1, 3 cycles of charge and discharge at 2.5V to 4.3V (wherein the initial charge is set to 0V to 4.3V) and 0.1C were performed. Thereafter, a cycle test was performed in the same manner as above within the battery voltage range of 2.5V to 4.2V. In this case, the assumed specific capacity of the positive electrode material was also set to 140mAh / g. Wherein, 1C = 140mA / g. The results are shown in Table 5.
[0237] (Example 3)
[0238] (V) (Full battery 2.5V to 4.5V, 0.1C, 3 cycles, cycle test 2.5V to 4.2V)
[0239] For the full battery assembled in the same manner as in Example 1, 2.5V to 4.5V (where the initial charge is set to 0V to 4.5V) and 0.1C charge and discharge are performed for 3 cycles, and then the cycle test is performed in the battery voltage range of 2.5V to 4.2V in the same manner as above. In this case, the assumed specific capacity of the positive electrode material is also set to 140mAh / g. Among them, 1C = 140mA / g. The results are shown in Table 5.
[0240] [Table 5]
[0241]
[0242] According to the results in Table 5, even when the assumed specific capacity of the positive electrode material is set to 140 mAh / g, the full battery of Example 1 shows better cycle characteristics than the full batteries of Comparative Examples 1 and 2 by pre-charging and discharging at 2.5 V to 4.4 V and 0.1 C for 3 cycles, compared with the case where the charging and discharging at 2.5 V to 4.4 V and 0.1 C are not pre-charged for 3 cycles.
[0243] The full cell of Example 1 has a higher specific capacity of the regenerated positive electrode material than the full cells of Examples 2 and 3, and can also maintain the above-mentioned retention rate after the cycle test at a high level.
[0244] On the other hand, compared with Example 2, the regenerated positive electrode material shows high cycle stability by undergoing a process of activating the battery at a higher voltage as in Example 1 and Example 3. It should be noted that it can be confirmed that a battery voltage higher than 4.6V is likely to greatly accelerate the decomposition of the electrolyte of the lithium ion secondary battery, so the maximum battery voltage in the activation process is preferably 4.3V to 4.5V, and more preferably 4.4V.
[0245] This international application claims priority based on Japanese Patent Application No. 2022-096429 filed on June 15, 2022 and Japanese Patent Application No. 2022-165994 filed on October 17, 2022, and the entire contents of Japanese Patent Application No. 2022-096429 and Japanese Patent Application No. 2022-165994 are incorporated herein by reference.
[0246] Description of Reference Numerals
[0247] 1Positive electrode collector
[0248] 2 Positive electrode
[0249] 3 Dividers
[0250] 4 Gasket
[0251] 5 Negative electrode
[0252] 6 Spacers
[0253] 7 Washers
[0254] 8 Negative electrode collector
[0255] 10Lithium-ion secondary battery
Claims
1. A regenerated positive electrode material, characterized in that: contain: lithium, nickel, cobalt and manganese; 0.3 mass % to 3 mass % aluminum; and Less than 1 mass % of at least one of copper and iron. 2 . The regenerated positive electrode material according to claim 1 , comprising at least one of calcium and magnesium, wherein the content of at least one of calcium and magnesium is 0.02 mass % or more and 0.1 mass % or less.
3. The regenerated positive electrode material according to claim 1 or 2, wherein: The aluminum content is 0.5 mass % or more and 2.5 mass % or less.
4. The regenerated positive electrode material according to claim 1 or 2, wherein: The lithium content is 5 mass % or more and 9 mass % or less.
5. The regenerated positive electrode material according to claim 1 or 2, wherein: The copper content is 0.01 mass % or less, The iron content is 0.6 mass % or less.
6. The regenerated positive electrode material according to claim 5, wherein: The copper content is 0.0005 mass % or more and 0.005 mass % or less, The iron content is 0.002 mass % or more and 0.6 mass % or less.
7. The regenerated positive electrode material according to claim 1 or 2, wherein: The content (mass %) of the aluminum (Al), the content (mass %) of the copper (Cu), and the content (mass %) of iron (Fe) satisfy the following formula: Al / (Al+Cu+Fe)≥0.
4. 8 . The regenerated positive electrode material according to claim 1 , comprising 50 mass % or more of the nickel, the cobalt and the manganese in total.
9. A method for producing a regenerated positive electrode material, characterized in that: The method for producing the regenerated positive electrode material according to claim 1 or 2 comprises the following steps: A heat treatment step of heat-treating the lithium-ion secondary battery to obtain a heat-treated product; A crushing step to obtain a crushed product by crushing the heat-treated product; A physical screening step, physically screening the crushed material to obtain a physically processed material; an acid treatment step, adding an acid solution to the physically treated product to obtain an acid treatment solution; an iron removal step, wherein an oxidant is added to the acid-treated solution, an alkali solution is added, and precipitation of iron hydroxide is filtered out; as well as In the alkali treatment step, the filtrate obtained after the iron removal step is mixed with an alkali solution.
10. The method for producing a regenerated positive electrode material according to claim 9, comprising: A lithium source adding step of adding a lithium source.
11. A method for using a regenerated positive electrode material, characterized in that: Including the following processes: An assembling step of assembling a lithium-ion secondary battery having the recycled positive electrode material according to claim 1 or 2; and In the activation step, the lithium ion secondary battery assembled in the assembly step is charged from a battery voltage of approximately 0V to 4.3V to 4.6V, and then charged and discharged within a battery voltage range of 0V to 3.5V to 4.3V to 4.6V.
12. A regenerated positive electrode, characterized in that: Contains the regenerated positive electrode material according to claim 1 or 2.
13. A lithium ion secondary battery, characterized in that: A regenerated positive electrode according to claim 12.
Citation Information
Patent Citations
Storage control system
JP1983047742B2
Game machine
JP2022096429A
High-level syntax design for point cloud coding
JP2022165994A